ANALISIS YURIDIS PUTUSAN BEBAS DALAM TINDAK PIDANA KORUPSI DI INDONESIA - Mulyo, Joyo (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The discrepancy in the application of the law in accordance with the provisions of the Corruption Crime Eradication Law is the imposition of an acquittal at the Central Jakarta District Court with an issue raised by the Public Prosecutor. The legal provisions regarding gratuities that have been stipulated in Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes juncto Article 64 paragraph (1) of the Criminal Code, because the element of "giving" in the first indictment is not proven then the element of "giving" in the first indictment applies mutatis mutandis to the consideration of the element of "giving" in the second indictment, especially in the substance of the notion of gratification. criminal sanctions, and the qualifications of the giver and recipient of gratuities, so that optimization of application and law enforcement is achieved, namely with a sense of justice and legal certainty. Bribery has a definition of a causal relationship from an act that results in or influences a person in his position as a state administrator for the interests of the bribe giver. Meanwhile, gratification should only be a gift, without having to associate any reciprocal actions. With a clear distinction between acts of bribery and pure gratuities that do not lead to bribery, the weight of the sentence against this is determined. Likewise for the giver of gratification, if it is said to be a bribe, it must be clear how much punishment will be given to him. For example, the Giver of Gratification as referred to in Article 12 B of Law no. 31 of 1999 as amended by Law no. 20 of 2001 concerning the Eradication of Corruption Crimes is the same as the recipient of gratuities. Thus the effect of the rules can be felt in balance because it destroys the supply and demand of prohibited actions.